4x-2-2x=x-6

Simple and best practice solution for 4x-2-2x=x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2-2x=x-6 equation:


Simplifying
4x + -2 + -2x = x + -6

Reorder the terms:
-2 + 4x + -2x = x + -6

Combine like terms: 4x + -2x = 2x
-2 + 2x = x + -6

Reorder the terms:
-2 + 2x = -6 + x

Solving
-2 + 2x = -6 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-2 + 2x + -1x = -6 + x + -1x

Combine like terms: 2x + -1x = 1x
-2 + 1x = -6 + x + -1x

Combine like terms: x + -1x = 0
-2 + 1x = -6 + 0
-2 + 1x = -6

Add '2' to each side of the equation.
-2 + 2 + 1x = -6 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = -6 + 2
1x = -6 + 2

Combine like terms: -6 + 2 = -4
1x = -4

Divide each side by '1'.
x = -4

Simplifying
x = -4

See similar equations:

| -7=z/5 | | 8-4=blank+2 | | (x*x)(-0.75*-0.75)=1 | | (-8)/(x^2-1)-(7)/(3-x) | | 8(x+3)=6 | | 15v-4/10=4/5 | | 49c^2-1=0 | | x+(x+1)+(x+2)=371 | | 5s+2=22 | | 2n^2=-2n | | .1387=(-9E-08x^2)+(.0007x)+(.1171) | | -11-1=10y-14-9y | | F(x)=(8) | | 2400/40=6600/n | | (3x*3x)+(2*2)-3=13 | | 2x+2-3x+3=3+2 | | 11*X^5+90*X^3+425*X-125=0 | | 1/2=4p | | X+1+3x=45 | | 8m=4(8m+24) | | 32/6 | | 5x^7/6-35=0 | | 15n-6-14n+7=11 | | 5x+7y=-11 | | 4m+20=5m+8 | | 3x^2=15x+2 | | k-15.6=4.9k | | ln(x)=4.2+ln(7.1) | | 30x^2-87x-54=0 | | 8x^5/2-56=0 | | 1.3t=0.45 | | 6x-65=61-x |

Equations solver categories